Vietnam’s Success in Attracting U.S. Semiconductor Investment: Strategic Lessons for Indonesia - Naufal Fikhri Khairi; Fredy Buhama Lumban Tobing (Andalas Journal of International Studies (AJIS), 2025)
Vietnam has been successful in attracting US investment in the semiconductor sector, as evidenced by the number of US chip companies opening factories there and by its acquisition of the International Technology Security and Innovation Fund (ITSI Fund). This makes Vietnam a key node in the global semiconductor supply chain due to the significant presence of US companies. Meanwhile, Indonesia has also been selected as a recipient of the ITSI Fund, but its implementation is still in the early stage, and US semiconductor companies have not yet invested in the country. This study aims to explain why Vietnam has succeeded in attracting US semiconductor investment and what lessons Indonesia can learn from this achievement. This study uses the Foreign Direct Investment (FDI) Theory from Schneider & Frey (1985) as an analytical tool to explain the success factors of Vietnam's semiconductor sector. This study uses a qualitative explanatory approach with a case study method, collecting data through document-based research and qualitative analysis. The findings indicate that Vietnam's success factors in the semiconductor sector lie in its progressive domestic economic development, stable domestic politics, and a coherent semiconductor policy. On the other hand, Indonesia faces various challenges in developing its semiconductor industry, including an ineffective bureaucracy, high levels of corruption, and the absence of a long-term roadmap for semiconductor industry development. Therefore, Indonesia can learn from several factors in Vietnam's success, particularly in establishing political stability, developing long-term planning, and increasing semiconductor cooperation with the United States.